Sensing up to 40 atm Using Pressure‐Sensitive Aero‐GaN. Issue 6 (12th March 2019) - Dragoman, Mircea; Ciobanu, Vladimir; Shree, Sindu; Dragoman, Daniela; Braniste, Tudor; Raevschi, Simion; Dinescu, Adrian; Sarua, Andrei; Mishra, Yogendra K.; Pugno, Nicola; Adelung, Rainer; Tiginyanu, Ion
Abstract : This work reports on the fabrication and characterization of a robust pressure sensor based on aero‐GaN. The ultraporous aeromaterial consists of GaN interconnected hollow micro‐tetrapods with the wall thickness of about 70 nm. The inner surface of hollow micro‐tetrapods contains an ultrathin film of ZnO genetically related to the sacrificial template used for epitaxial deposition of GaN. The pressure sensing measurements disclose a nearly linear dependence of the electrical conductance versus applied pressure up to 40 atm, a stable state signal being attained after an interval of about 10 s. Abstract : A robust pressure sensor is developed by using GaN aerogel prepared by epitaxial deposition of gallium nitride on sacrificial zinc oxide micro‐tetrapods. Its relatively high nondimensional sensitivity (16.2 × 10 −3 at 5 atm and 7.4 × 10 −3 at 40 atm) in conjunction with currents as high as tens of milliamperes makes GaN aeromaterial feasible for exploitation in portable electrical equipment.